Short-term effects of pet acquisition and loss on well-being in an unbiased sample during the COVID-19 pandemic - Judit Mokos; Eniko Kubinyi; Dorottya J. Ujfalussy; Ivaylo B. Iotchev; Borbála Paksi; Zsolt Demetrovics; Róbert Urbán; Ádám Miklósi (Scientific Reports)
Abstract Research on the impact of pet ownership on well-being has produced mixed results, often influenced by a focus on pet enthusiasts. To address this bias, we conducted a longitudinal study in Hungary using a stratified random sample based on gender, age, education, and settlement type. Unlike previous studies, our participants were not particularly devoted to pets and were not necessarily the primary caretakers, offering a more balanced perspective on how pet acquisition affects well-being. Among the 2783 respondents who participated three times in data collection, 65 acquired a pet, and 75 lost a pet during the COVID-19 pandemic. Pet acquisition initially increased cheerfulness, but this effect was short-lived, lasting only 1–4 months. Over a longer period (up to 6 months), pet acquisition—particularly dog acquisition—was linked to declines in calmness, activity, cheerfulness, and life satisfaction. Importantly, neither mental nor physical well-being was linked to future pet acquisition, and losing a pet had no significant effect on well-being. These findings challenge the widely held belief that pet acquisition leads to lasting improvements in well-being, suggesting instead that the demands of pet care—especially for dogs—can outweigh initial benefits. Moreover, the results underscore the context-dependent nature of the human-animal bond. The stress and uncertainty of a global crisis may alter the typical emotional and psychological benefits of pet ownership.